Hacks for minecrafters ebook The unofficial guide to tips and tricks that other guides won't teach you. - Miller, Megan (2014)
A New York Times bestseller, revised and updated, the ultimate book of secrets for boys and girls who plays Minecraft! NOT OFFICIAL MINECRAFT PRODUCT. NOT APPROVED BY OR ASSOCIATED WITH MOJANG. With hundreds of millions registered players, Minecraft is one of the world's most popular games. This updated guide will help them all with new function and crafting systems, illusioners, parrots, and building materials like glazed terracotta and concrete. In this hacker's guide, you'll find expertise on: Mining—including diamonds and rare minerals! Farming—growing tricks, seed hacks, and the best tree-replanting techniques! Battle—for the best weapons and armor! Magic—top crafting hacks and book modifiers! You will never be stuck again! With more than one hundred full-color screenshots of in-game footage, you'll be able to carefully follow every tip with precision. It doesn't matter if you're playing on a PC, mobile device, or home console; with Hacks for Minecrafters , you'll be beating the game in no time. Every block has been accounted for, all living entities have been taken into consideration, and all modes of game-play are covered!